AKTIVITAS ANTIJAMUR MINYAK ATSIRI SEREH WANGI (CYMBOPOGON NARDUS (L.) RENDLE) - Lely, Nilda; Sulastri, Hetty; Meisyayati, Sari (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Citronella fragrance is one of the many plants in Indonesia. Citronella fragrance is widely used by Indonesian people as a spice dish and has traditionally been used for various treatments. Citronella fragrance contains essential oils that have the potential to have anti-fungal effects and have traditionally been used for the treatment of skin diseases. Isolation of citronella essential oil with the method of vapor distillation. The tested fungi are opportunistic fungi that often infect human skin. In testing the antifungal activity of the citronella essential oil (Cymbopogonnardus (L.) Rendle) against the fungal causing skin infection. The research was done by using agar diffusion method and using the density disc as the diffusion medium against A research of antifungal?s activity of essential oil of citronella (Cymbopogon nardus (L.) Rendle ) to fungus that cause disease in humans has been done. This research used agar diffusion method to the fungus test Tricophyton rubrum, Tricophyton mentagrophytes and Candida albicans. The concentration that used 1%, 0,5%, 0,25% and 0,1%. The results showed that in concentration 1% essential oil of citronella (Cymbopogon nardus ( L.)Rendle) has the highest activity with Candida albicans with an average of inhibition diameter was 19,4mm  ± 0,15. In 0,1% concentration of essential oil of citronella (Cymbopogon nardus (L.) Rendle) does not have antifungal?s activity to Tricophyton mentagrophytes that without inhibition diameter around the paper discs. Meanwhile, in concentration 0,1%, the essential oil of citronella (Cymbopogon nardus (L.) Rendle) still have antifungal?s activity to Tricophyton rubrum and Candida albicans with an average of  inhibition diameter 7,4 mm ±  0,35 dan 8,5 mm ±  0,15. Keywords: Candida albicans, Sereh wangi (Cymbopogonnardus (L.), Tricophyton                      rubrum, Tricophyton mentagrophytes, Candida albicans